Oxygen free-radicals mediate an inhibition of proteoglycan synthesis in cultured articular cartilage. Issue 3 (June 1984) - Bates, E J; Lowther, D A; Handley, C J
Abstract : Superoxide radical, generated enzymatically by the action of xanthine oxidase on hypoxanthine, significantly inhibited proteoglycan synthesis by cultured bovine articular cartilage. This inhibition was not due to the generation of uric acid or to the generation of superoxide per se. It was immediate in onset and still evident after six days in culture. The inhibition was similar for both 35S-sulphate and 3H-acetate incorporation into glycosaminoglycans and could not be reversed by addition of beta-D-benzyl xyloside. Protein synthesis was also inhibited.